2020
DOI: 10.1177/0363546519896355
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Radiographic Findings of Structural Hip Deformities for Femoroacetabular Impingement in Patients With Hip Pain

Abstract: Background: Radiography is the initial imaging modality used to evaluate femoroacetabular impingement (FAI), and diagnostic radiographic findings are well-established. However, the prevalence of these radiographic findings in patients with hip pain is unknown. Purpose: The purpose was 3-fold: (1) to determine the overall prevalence of radiographic FAI deformities in young patients presenting with hip pain, (2) to identify the most common radiographic findings in patients with cam-type FAI, and (3) to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 54 publications
(88 reference statements)
0
33
1
1
Order By: Relevance
“…8 The prevalence of radiographic findings consistent with FAI in a large cohort of patients presenting with hip pain was recently found to be 60.5%. 30 The percentage of patients with FAI syndrome in the present study was less than that in the studies evaluating radiographs only. This is an expected finding since it is known that many asymptomatic patients have findings consistent with FAI on radiographs alone.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…8 The prevalence of radiographic findings consistent with FAI in a large cohort of patients presenting with hip pain was recently found to be 60.5%. 30 The percentage of patients with FAI syndrome in the present study was less than that in the studies evaluating radiographs only. This is an expected finding since it is known that many asymptomatic patients have findings consistent with FAI on radiographs alone.…”
Section: Discussioncontrasting
confidence: 65%
“…8,12,15 One study reported the prevalence of radiographic parameters of structural deformity in patients with hip pain. 30 However, the clinical diagnosis of FAI syndrome requires the presence of a triad of clinical symptoms, physical examination signs, and imaging findings. 11 We are aware of 1 study that reported the incidence of true FAI syndrome, although this was in a small cohort and the radiographic parameters were not well-defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Even so, plain radiography of the pelvis in its different projections has been the most widely used imaging method for the radiographic detection of these anatomic variations in studies with large samples. 59 The radiographic findings associated with FAI observed on plain film radiographs include the following for the camtype variant: an increased alpha angle, a pistol-grip deformity (PGD) of the femoral head-neck, a low femoral headto-femoral neck ratio (FHFNR), lateral flattening of the femoral head (LFFH; coxa recta), focal prominence of the femoral neck (FPFN), and coxa vara defined by the femoral neck-shaft angle (NSA; also called the caput-collumdiaphyseal angle). For the pincer-type variant, the findings include the following: an increased lateral center-edge angle (LCEA; Wiberg angle); a decreased acetabular index (AI; Tö nnis angle); the crossover sign (COS; figure-of-8 sign); the posterior wall sign (PWS); excessive acetabular coverage (EAC) and its variant, os acetabuli; the ischial spine sign; coxa profunda; and protrusio acetabuli.…”
mentioning
confidence: 99%